2006
DOI: 10.3354/meps319225
|View full text |Cite
|
Sign up to set email alerts
|

Growth-dependent recruitment of Pacific bluefin tuna Thunnus orientalis in the northwestern Pacific Ocean

Abstract: To estimate the survival process of Pacific bluefin tuna Thunnus orientalis during the larval period, estimated growth histories were compared between larvae collected in late spring and juveniles collected in the boreal summer of 2004, which were considered to be survivors of the larval cohorts. Larval tuna (3.3 to 9.6 mm standard length, SL) were collected from mid-May to early June around the Ryukyu Islands, northwestern Pacific Ocean, and juvenile tuna were collected offshore of Kochi and Nagasaki prefectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 26 publications
3
74
1
Order By: Relevance
“…The primary spawning ground of this species is in the northwest region of the Philippine Sea, between eastern Tai-wan and Ryukyu Islands in the southern part of Japan (roughly the western North Pacific, Fig. 1, Bayliff 1994, Chen et al 2006, Tanaka et al 2006, Shiao et al 2010. Spawning occurs in late April to July at a sea surface temperature of 26 ± 2°C, which has been confirmed in rearing experiments ).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The primary spawning ground of this species is in the northwest region of the Philippine Sea, between eastern Tai-wan and Ryukyu Islands in the southern part of Japan (roughly the western North Pacific, Fig. 1, Bayliff 1994, Chen et al 2006, Tanaka et al 2006, Shiao et al 2010. Spawning occurs in late April to July at a sea surface temperature of 26 ± 2°C, which has been confirmed in rearing experiments ).…”
Section: Introductionmentioning
confidence: 86%
“…This difference was also observed in Pacific bluefin tuna spawning in the northwest region of the Philippine Sea, between eastern Taiwan and Ryukyu Islands located in the southern part of Japan (roughly the western North Pacific) from late April to June (Bayliff 1994, Chen et al 2006, Tanaka et al 2006, Shiao et al 2010 and in the southern Sea of Japan in late July to August (Tanaka et al 2007, Itoh 2009). These 2 areas have different temperatures and salinities.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, ARs increased to 6.7 on average for fish > 200 cm, which were approximately 9 yr old (Shimose et al 2009). Tanaka et al (2006) reported that 16.7− 30.0 cm PBT appeared in waters off Kochi Prefecture at 54 to 89 d of age. Therefore, taking the slope value into consideration, it is suggested that they grow rapidly and gain greater swimming ability in the 1 to 2 mo after arriving in Japanese coastal waters.…”
Section: Discussionmentioning
confidence: 99%
“…Post & Prankevicius 1987, Hovenkamp 1992, Meekan & Fortier 1996, Sirois & Dodson 2000b, Searcy & Sponaugle 2001, Takasuka et al 2003, Meekan et al 2006, Shoji & Tanaka 2006a, Tanaka et al 2006, Robert et al 2007). However, many studies shown that the survivors were rather the slow-growing members of a cohort (e.g.…”
Section: Introductionmentioning
confidence: 99%